Small entrepreneurship in hospitality: Croatian experiences - Slobodan Ivanovic; Eddy Rot; Miroslav Pretula (UTMS Journal of Economics, 2013)
After introductory explanations regarding the selection problems of small enterprises in the Croatian hotel industry, the author provides a number of key indicators of their role in improving the competitiveness of the Croatian hotel industry in the global tourism market. In developed tourism countries, small enterprises have a dominant share in the structure of the hotel industry, and their importance is growing even in the former socialist countries of Europe. Small hotels in Italy accounted for more than 50%, and in Austria with more than 70% of lodging facilities and represent a generator of hotel business in a large number of European tourism countries, and great attention is given to the small enterpreneurs stimulating their growth with different measures of tourist and general economy politics. The author reflects on the Croatian experience of the small businesses in the hospitality through research of development of small family hotels and their importance for the improvement of the supply of the Croatian hotel industry which future is built on personal approach to guests and present trends in the tourism market. States that the role of the National Association of family and small hotels, which represents the specific interests of small hoteliers and enables the continuous improvement of the quality of their offerings, as well as measures to encourage small business development at the macro level. Based on the made analysis the measures of increasing the efficiency of small businesses in the Croatian hospitality are given.
Keywords: L83; 330; small businesses; the Croatian hospitality; small and family-run hotels; development incentives